Kajian Soal Pada Buku Teks Matematika Siswa Kelas VII Semester 2 Kurikulum 2013 (Edisi Revisi 2016) Menggunakan Framework Pisa - Ermawati, Dian; , Prof. Dr. Budi Murtiyasa, M.KOM (2017)
This study aimed to describe the suitability of the questions in the seventh grade mathematics textbook 2nd semester of curriculum 2013 (revised edition 2016) based on PISA framework. The instrument used was the aspect PISA assessment consisting of aspects of the content, process and context with its categories. The research method was descriptive analysis. Technical analysis of data is done in three stages: data reduction, data presentation and conclusion. The data was collected by documentation of the book. The results showed that problems in the seventh grade mathematics textbook 2nd semester of curriculum 2013 (revised edition 2016) is suitable with the PISA framework. Aspect Content is dominated by changes and relationships. The process employs concepts, facts, procedures and reasoning more dominant than the others. Aspects context dominated by the general context. Keywords: mathematics textbook, analysis textbook, framework PISA